Features of Linking words in “Jane Eyre” novel by Charlotte Bronte and the Vietnamese equivalents / Nguyễn Thị Thu Phương; NHDKH Dr Nguyễn Thị Thu Hương - Nguyễn, Thị Thu Phương
In this thesis, the writer will study about features of linking words in “Jane Eyre” novel by Charlotte Bronte and comparison with Vietnamese. In fact, linking words have an important role in language grammar. Since then, have not seen a public dissertation research about linking words. Therefore, the study is expected to provide Vietnamese learners with the approaches of translating linking words and some ways to help Vietnamese learners of English overcome the difficulties in translating English linking words. The researcher also hopes to provide teachers and students with knowledge of the translation of English linking words. To do all these things, the writer use descriptive and analytic to the study. Description is intended to follow a qualitative approach. The data are collected, the description of the translation of linking words is given. The results of the study suggest some approaches of translating linking words and some ways to help Vietnamese learners of English overcome the difficulties when using linking words.